Promoting Transition Resilience through Personal Development Planning: An Evaluation of the Perspectives of Preparation for Transition of Final-Year Undergraduate Nursing Students - Leigh, Jacqueline; Darvill, Angela (International Journal of Practice-based Learning in Health and Social Care, 2019)
The experience of transition is of concern to newly registered nurses entering the world of work, and to those seeking to prepare, recruit and retain such nurses. This paper evaluates a final-year preparation for role transition module from the perspectives of final-year student nurses. Focus groups and one-to-one interviews were carried out at three distinct points in time, after the module assessments and after each of the three clinical placements in the final year. Braun and Clarke’s inductive thematic analysis was used to analyse the data with four themes emerging: impact/relevance of the personal development plan; development of self; role of the mentor; and transition resilience/taking control. These four themes were then applied to Kirkpatrick’s model of evaluation, providing a deductive or theoretical framework for analysing and evaluating the outcomes of the module. Preparation for transition and the development of resilience have been identified as a potential solution associated with the negative experiences and challenges of transition. Resilience is an essential attribute that enables nurses to make sense of their experiences of transition and manage the stress of the workplace. Creating transition-focussed personal development plans to guide learning in the final year enabled the participants to take responsibility for their own learning, and, with the support from a good mentor, participants were able to understand that feeling nervous about transition was normal. This in turn enhanced their confidence, promoting ‘transition resilience’ as opposed to feelings and experiences associated with the more traditional concept of transition or reality shock.